(untitled) (Palíndromo, 2013)
This article aims to analyze some artworks by Cildo Meireles and Hélio Oiticica during the cultural resistance period in dictatorial Brazil (1964-1985). To do so we will take in account the period of Brazilian military dictatorship as a time of state of emergency, so well conceptualized by Italian philosopher Giorgio Agamben, which we will use in this article. We intend to get to a better understanding about the guerrilla art by Cildo Meireles and Hélio Oiticica during dictatorial Brazil.